Ventricular function and high-sensitivity cardiac troponin T in preterm infants with neonatal sepsis - Nusarintowati Ramadhina; Rubiana Sukardi; Najib Advani; Rinawati Rohsiswatmo; Sukman T. Putra; Mulyadi M. Djer (Indonesian Pediatric Society, 2015)
Background Hemodynamic instability in sepsis, especially in the neonatal population, is one of the leading causes of death in hospitalized infants. The major contribution for heart dysfunction in neonatal sepsis is the myocardial dysfunction that leads to decreasing of ventricular function. The combination of echocardiography and laboratory findings help us to understand the ventricular condition in preterm infants with sepsis.Objective To assess for a correlation between ventricular function and serum high-sensitivity cardiac troponin T (hs-cTnT) level in preterm infants with neonatal sepsis.Methods We prospectively studied 30 preterm infants with neonatal sepsis who were admitted to the neonatal intensive care unit (NICU) of Cipto Mangunkusumo Hospital from June 1 – August 31, 2013. The ventricular functions were measured using 2-dimensional echocardiography. The parameters of right ventricular (RV) function assessment were tricuspid annular plane systolic excursion (TAPSE) and RV myocardial performance index (MPI). For left ventricular (LV) performance, we assessed ejection fraction (EF), fractional shortening (FS), and LV-MPI. Serum hs-cTnT was measured and considered to be a marker of myocardial injury.Results Subjects had a mean gestational age of 31.5 (SD 2.18) weeks and mean birth weight of 1,525 (SD 437.5) g. The mean LV function measured by MPI was 0.281 (SD 0.075); mean EF was 72.5 (SD 5.09)%; and mean FS was 38.3 (SD 4.29)%. The RV function measured by TAPSE was mean 6.85 (SD 0.94) and that measured by MPI was median 0.255 (range 0.17-0.59). Serum hs-cTnT level was significantly higher in non-survivors than in survivors [282.08 (SD 77.81) pg/mL vs. 97.75 (24.2-142.2) pg/mL, respectively P =0.023]. There were moderate correlations between LV-MPI and hs-cTnT concentration (r=0.577; P=0.001), as well as between RV-MPI and hs-cTnT concentration (r=0.502; P=0.005). The positive correlation between LV and RV-MPI in neonatal sepsis was strong (r=0.77; P <0.001).Conclusion Left and right ventricular MPI show positive correlations with hs-cTnT levels. Serum hs-cTnT is significantly higher in non survivors. As such, this marker may have prognostic value for neonatal sepsis patients.